Komunikasi penyiaran dakwah dalam sejarah islamisasi di daerah perbatasan Indonesia-Malaysia pada masa kerajaan - Zakaria Efendi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
As is known, the border area of Indonesia and Malaysia in West Kalimantan is an area that is included in the underdeveloped, outermost, and leading (3T) areas. At some points in the border area, Islam has become a religion embraced by minority communities because the indigenous people who live come from the Dayak tribe who do not embrace Islam. However, at other border points, Islam became the majority religion, such as in the Sambas border area, because there was an Islamic kingdom, namely the Sambas Sultanate. Islam is present in the border area can not be separated from the influence of the Islamic Kingdom in West Kalimantan in the past. Therefore, this study aims to describe the communication of da'wah broadcasting in the history of Islamization at the border using communication analysis, while the approach method uses descriptive qualitative methods. The results of the study: (1) the history of the development of Islam in border areas cannot be separated from the role of Islamic da'wah carried out by Islamic kingdoms in West Kalimantan, (2) the Islamic Kingdom became the most contributing media in broadcasting Islam in the past, the influence of The Islamic Kingdom in West Kalimantan still remains today, 3) Political and economic power in the Islamic Kingdom is the most effective medium used in carrying out the Islamization mission in West Kalimantan to the border areas. The conclusion of this study is that the Islamic kingdoms in West Kalimantan played a role as a medium in the process of developing Islam in West Kalimantan and border areas, the power in the kingdom became a very influential medium in the success of broadcasting Islam. So that Islam becomes a religion that is embraced by the majority of people at several border points.